2019
DOI: 10.18326/rgt.v12i1.28-48
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedbacks and Grammar Teaching in a Situated Teaching Context of Process-Based Writing

Abstract: This study was aimed at finding out 1) how learners in a specific teaching-learning context namely process-based academic essay writing perceived the importance of corrective feedbacks (CF); 2) what CF was expected the most; 3) in what way learners preferred to have their CF  provided; and 4) how learners perceived the importance of grammar teaching. It was conducted at English Literature Department of a university in Central Java Indonesia. Forty two students who were taking Essay Writing course served as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Most of the students also fixed their drafts, but some students also tried to revise their drafts using automated online feedback such as google docs, Grammarly, etc. These interview results are in line with Jodaie et al (2011), Mohammad and Rahman (2016), Elhawwa et al (2018), Listiani (2017), Luan and Ishak (2018), Tursina et al (2019), Hartono et al (2019, Sabarun (2020), & (Yunus, 2020) stating that most of the students had positive attitudes towards their lecturer direct corrective feedback because it is very helpful, beneficial for the learners; students preferred to have comprehensive, direct, and specific feedback; and students also felt satisfied. This finding supports idea that by giving direct corrective feedback, the students will acquire grammar with specific features (Sheen, 2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most of the students also fixed their drafts, but some students also tried to revise their drafts using automated online feedback such as google docs, Grammarly, etc. These interview results are in line with Jodaie et al (2011), Mohammad and Rahman (2016), Elhawwa et al (2018), Listiani (2017), Luan and Ishak (2018), Tursina et al (2019), Hartono et al (2019, Sabarun (2020), & (Yunus, 2020) stating that most of the students had positive attitudes towards their lecturer direct corrective feedback because it is very helpful, beneficial for the learners; students preferred to have comprehensive, direct, and specific feedback; and students also felt satisfied. This finding supports idea that by giving direct corrective feedback, the students will acquire grammar with specific features (Sheen, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…All of them were conducted in an experimental study. Additionally, (Listiani, 2017), (Tursina et al, 2019), (Hartono et al, 2019), and (Sabarun, 2020) found that university students are satisfied, preferred to be given direct corrective feedback, and felt assessed after being given the direct corrective feedback in their writing. In line with the previous finding, Yunus (2020) found that high school students are preferred to be given direct corrective feedback since it is comprehensive and easier to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the practice of providing feedback as an assessment, many students still prefer teacher feedback rather than other types of feedback because it is more comprehensible, detailed, and helpful to revise their drafts [11], [12], [13], [14], [15], [16], [17], [18], [19], [20]. In contrast with teacher feedback, many students do not prefer peer feedback because peer feedback is too subjective and uncritical, so some students cannot understand the given feedback (Kuyyogsuy, 2019; Kaya & Yaprak, 2020; Keskin, 2022) which lead the students to discourage and disengage with peer feedback practices.…”
Section: Introductionmentioning
confidence: 99%